A biomechanical analysis of the 1984 U.S. Olympic freestyle distance swimmers - Maglischo, C. W.; Maglischo, E. W.; Higgins, J.; Hinrichs, R.; Luedtke, D.; Schleihauf, R. E.; Thayer, A. (Swimming Science V, 1988)
The propulsive efficiency of competitive swimmers has been a matter of considerable interest for many decades (Alley, 1952; Plagenhoff, 1971; Barthels & Adrian, 1974; Schleihauf, 1978; Schleihauf et al., 1985). In 1974, Schleihauf introduced a method for estimating the instantaneous propulsive force that is generated by swimmers as they stroke down the pool. This method is based on using vector analysis to solve for the resultant and propulsive forces when the velocity, direction, and angle of attack of the hand and arm are known. Schleihauf' s method was used to study the propulsive effectiveness of selected members of the 1984 U.S Olympic Swimming Team while they attended a pre-games training camp in Mission Viejo, California during July 1984. The project was funded by United States Swimming with the permission of the athletes and coaching staff. The Sports Medicine Committee of United States Swimming selected the authors to conduct the investigation. The purpose of this paper was to present the results from the distance freestyle swimmers.